Protein Phosphatase 2A in the Regulatory Network Underlying Biotic Stress Resistance in Plants - Durian, Guido; Rahikainen, Moona; Alegre, Sara; Brosché, Mikael; Kangasjärvi, Saijaliisa (Frontiers in Plant Science, 2016)
Biotic stress factors pose a major threat to plant health and can significantly deteriorate plant productivity by impairing the physiological functions of the plant. To combat the wide range of pathogens and insect herbivores, plants deploy converging signalling pathways, where counteracting activities of protein kinases and phosphatases form a basic mechanism for determining appropriate defensive measures. Recent studies have identified Protein Phosphatase 2A (PP2A) as a crucial component that controls pathogenesis responses in various plant species. Genetic, proteomic and metabolomic approaches have underscored the versatile nature of PP2A, which contributes to the regulation of receptor signaling, organellar signaling, gene expression, metabolic pathways and cell death, all of which essentially impact plant immunity. Associated with this, various PP2A subunits mediate post-translational regulation of metabolic enzymes and signalling components. Here we provide an overview of protein kinase/phosphatase functions in plant immunity signalling, and position the multifaceted functions of PP2A in the tightly inter-connected regulatory network that controls the perception, signalling and responding to biotic stress agents in plants.